The effect of nitrogen input on chemical profile and bioactive properties of green- and red-colored basil cultivars - Cruz, Luís Royer Oliveira (2018)
In the present study, three red-colored (Dark Opal, Basilico Rosso, and Red Basil) and one green-colored landrace (Mitikas) of basil (Ocimum basilicum L.) were grown under four nitrogen regimes, namely Control (no fertilizer added), 200 ppm, 400 ppm, and 600 ppm of nitrogen (N). Fresh yield varied depending on N input following a quadratic function in all four genotypes, and green basil performed better compared to the red cultivars. A significant interaction of genotype-N input was recorded for most of the chemical parameters measured. Tocopherols contents of leaves were consistently higher in plants that received 200 ppm of N and lower in those receiving 600 ppm of N, especially in Dark Opal and Red Basil cultivars. Polyunsaturated fatty acids (PUFA) were the major category of fatty acids and Red Basil had the lowest ratio of omega-6/omega 3 (0.29) and thus the best fatty acid profile. Polyphenols content was the highest in Red Basil and Dark Opal (25 mg/g of extract on average) and the lowest in Mitikas and decreased with increasing N input. Similarly, antioxidant activity was the highest in Dark Opal and Red Basil fertigated with 200 ppm of N, whereas all the leaf extracts tested had good antibacterial and antifungal activity. In conclusion, basil chemical and bioactive profile was significantly influenced by both genotype and N input. Red-colored basil, although less productive, had the best chemical profile, and moderate levels of N input may provide the best compromise between yield, nutritional value, and bioactivity for the species.